Clostridium difficile outbreak caused by NAP1/BI/027 strain and non-027 strains in a Mexican hospital - Morfin-Otero,Rayo (2016)
Abstract Background Clostridium difficile infections caused by the NAP1/B1/027 strain are more severe, difficult to treat, and frequently associated with relapses. Methods A case–control study was designed to examine a C. difficileinfection (CDI) outbreak over a 12-month period in a Mexican hospital. The diagnosis of toxigenic CDI was confirmed by real-time polymerase chain reaction, PCR (Cepheid Xpert C. difficile/Epi). Results During the study period, 288 adult patients were evaluated and 79 (27.4%) patients had confirmed CDI (PCR positive). C. difficilestrain NAP1/B1/027 was identified in 31 (39%) of the patients with confirmed CDI (240 controls were included). Significant risk factors for CDI included any underlying disease (p < 0.001), prior hospitalization (p < 0.001), and antibiotic (p < 0.050) or steroid (p < 0.001) use. Laboratory abnormalities included leukocytosis (p < 0.001) and low serum albumin levels (p < 0.002). Attributable mortality was 5%. Relapses occurred in 10% of patients. Risk factors for C. difficileNAP1/B1/027 strain infections included prior use of quinolones (p < 0.03). Risk factors for CDI caused by non-027 strains included chronic cardiac disease (p < 0.05), chronic renal disease (p < 0.009), and elevated serum creatinine levels (p < 0.003). Deaths and relapses were most frequent in the 027 group (10% and 19%, respectively). Conclusions C. difficile NAP1/BI/027 strain and non-027 strains are established pathogens in our hospital. Accordingly, surveillance ofC. difficile infections is now part of our nosocomial prevention program.